Immune evasion in colo-rectal cancer in a cohort of Sudanese patients: possible roles for MHC Class II antigens - Dafalla, Mohammed; Elzaki, Kamal; Mohamed, Elsagad; Elsafi, Mohamed; Mohamed, Hatim; Younis, Brima; van Niekerk, Chantal; Steenkamp, Vanessa; Musa, Ahmed; Khalil, Eltahir (International Journal of Medicine, 2017)
Background: Colorectal cancer (CRC) is the third most common cancer world-wide. The majority of cases occur in the developed world. This prospective study aimed to correlate different human leukocyte antigens (HLA types; HLA DRB1 and DRB3) with the aggressiveness of CRC in Sudanese patients.Methods: Thirty-three patients with histopathologically confirmed CRC were included in the study. Demographic, clinical and laboratory data were recorded. Molecular typing for HLA DRB1 (DR1, 7 and 17), DRB3 and DRB4 were carried out using PCR-based Sequence-Specific Primers.Results: Forty percent of the patients were â‰¤ 50years; with a male to female ratio of 2.5:1. Rectal bleeding was the commonest presenting symptom. While moderately differentiated adenocarcinoma was the dominant histological type. Duke's stages B and C were reported in 54.6% and 42.4% of patients, respectively. No patients presented with Dukes stages A or D. HLA DRB3 was the most frequent allele detected followed by DRB4 and DR17. A higher frequency of the DRB3 allele was found in the peripheral blood when compared with the tumor and apparently normal tissues. HLA DRB3 and DR7 allele frequencies correlated with Duke's stages B and C but not with age, sex or degree of differentiation, while blood DR17 antigen correlated only with the degree of tumor differentiation.Conclusion: CRC was found to have a higher occurrence in younger patients.Â  Tumors were aggressive with advance Duke's stage at presentation. This aggressive nature could possibly be related to either increased HLA DRB3 or DR7 or decreased HLA DR17 levels in the tumor tissue when compared with the blood. No differences between tumor and normal colon tissues were found, in concordance with the multifocally of colon cancer theory.